UJARAN TABU DALAM RITUAL ADAT PURUNG TA KADONGA RATU KAJIAN ANTROPOLOGI LINGUISTIK - KARERI, ELITE; Djuli, Labu; Makan Malay, Narantoputrayadi (Jurnal Lazuardi, 2025)
This research, entitled “Taboo Utterances in the Purung Ta Kadonga Ratu Traditional Ritual: An Anthropolinguistic Study,” aims to identify, describe, and analyze the forms and meanings of taboo utterances used in the Purung Ta Kadonga Ratu ritual of the Anakalang community in Central Sumba Regency. The study employs an anthropolinguistic approach, combining linguistic analysis with socio-cultural context to understand how taboo language functions in maintaining sacredness and social order within traditional ceremonies.The research applies a qualitative descriptive method. Data were collected through in-depth interviews, direct observation and documentation involving three key informants: traditional elders and ritual leaders. The data were analyzed through transcription, translation, classification and interpretation of the taboo utterances, based on Kridalaksana’s (1993) theory and Hymes’s (1972) SPEAKING communication model.The findings reveal 28 main taboo utterances, consisting of 19 positive (sacred) taboos and 9 negative (socially prohibited) taboos. Positive taboos are associated with sacred elements, respect toward God, ancestors and cultural symbols—such as Loda Pari, Mamuli and Labba. Negative taboos, on the other hand, are linked to prohibitions against words or expressions believed to bring misfortune or offend ancestral spirits, such as Mehang Karaga, Ratu Hanguju and Patara Mata Madu.These findings demonstrate that taboo utterances serve as a means to preserve ritual sanctity, regulate social behavior and symbolize reverence toward ancestral and cultural values. Thus, linguistic taboos in the Anakalang community reflect not only linguistic structure but also their belief system, ethics and collective cultural identity.